(untitled) (Rivista Italiana di Filosofia Analitica Junior, 2018)
With the current paper we will intend i) to elaborate a critical examination of the alleged use of transparency as independent of any epistemological view in favor of evidentialism, ii) to remark the inadequacies of the Absjørn Steglich-Petersen’s attempt to replace the concept of belief with that of truth in reflective contexts in response to the claim of some evidentialist who want to use transparency to support their own dialectical purposes, and iii) to suggest a new approach to transparency which allows us to expand the theoretical horizons in which philosophical research on the subject has so far moved.